Effect of COVID 19 lockdown on medical education; a systematic review - Shakeel, Faiz; Saghir, Iqra; Toufique, Ghassan; Nabiha Khalid; Kalas, Zunain Ali (Journal of the Pakistan Medical Association, 2023)
Objectives: To evaluate the complications of e-learning during pandemic-led lockdown, its effect on medical students’ learning, and to recommend practical solutions. Method: The systematic review comprised literature search on Google Scholar, Medline and Pubmed databases for studies published from 2019 to April, 2022. dealing with the effect of coronavirus disease-2019 on medical education. Key phrases used were ’COVID19 effects’, ‘medical students’ or ’e-learning’ or ’e-examination’. Methodological information was evaluated using EPPI (Evidence for Policy and Practice Information) tool. Results: Of the 60 studies initially found, 5(8.33%) were included. Students in their final year required practical application to benefit their professional lives. As a result, this circumstance has a variety of psychological consequences, such as an inability to focus during self-study for final-year test preparation, which leads to a loss of self-confidence and identity, and an inability to develop into tomorrow’s competent and professional doctor. Conclusion: Despite emergencies like the pandemic, the students’ future should not be ignored. They need practical education for future work. There is a need for better strategies for improved learning so that future doctors may work efficiently in their fields. Key Words: COVID-19, Health lockdown. e-learning, Medical, PRISMA, Team-based learning, 3D learning, Psychological effects.